The morphological and surface roughness of magnetorheological polished AISI 6010 surface - Soffarina M., Soffie; Izwan, Ismail; Nurain, Mutalib; Syarifah N., Aqida (Malaysian Tribology Society (MYTRIBOS), 2020)
This paper discussed the morphological and surface roughness produced on AISI 6010 aluminium surface with microgroove using the magnetorheological polishing method. Initially, the 17 samples were prepared with micro v-groove features using CNC (computer numerical control) milling machine. Box-Behnken design of experiment (DOE) was used to vary the polishing process factors namely; speed, voltage, and magnetic field. The DOE allows a relationship on morphological and surface roughness to be studied. The MRP process is carried out using fabricated 1 axis 2 d.o.f MRP rig mounted on a CNC machine. Abrasive added MRP fluid was used during the polishing process. The surface roughness, Ra, of the samples was measured under an Olympus 3D laser microscope. From morphology study, the irregularities on v-groove and the flat surface of 17 samples after MRP were reduced. The magnetorheological polishing process reduced surface roughness from 10 μm to as low as 0.4 μm with a constant polishing time of 10 minutes. This study shows that the MRP method is capable to replace the conventional polishing process to polish complex micro features on Al 6010 surface.